Pengaruh Suhu Dan Persen Katalis Karbon Aktif Terhadap Yield Pirolisis Limbah Plastik Polypropylene (PP) - Ade Maulana; Syarfi Daud; Ivnaini Andesgur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The increasing amount of plastic waste raises its own problem for the enviroment. The prolem is caused by the difficulty of biologically decomposing of the plastic waste. Various efforts have been made to reduce plastic waste. One way to use plastic waste is to process it into liquid fuel through the pyrolysis process. The study aims to determine the effect of each temperature variation and percent of catalyst from the activated carbon on the yield produced by the polypropylene type plastic, and characterization of the resulting liquid fuel. The pyrolysis was carried out at a temperature variation of 3000C, 3500C, 4000C, and the percent of the catalyst variaton from the activated from 5%, 6%, 7%, and without the catalyst, with a reation time of 120 minutes. The results of this study produced the highest yield of 70,03% at 4000C by adding catalyst from activated carbon by 7%. The characterization of the fuel produced was 0,870 gram/ml in density, kinemati viscosity at 2,868 eSt, flash point at 520C, and calor value at 44,696 Mj/kg.Keyword: liquid fuel, heating value, pyrolysis, polypropylene, active carbon.